Blessed and called to be a blessing : Muslim-Christian couples sharing a life together. - Richmond, Helen (Regnum Books International, 2015)
Christians and Muslims, bound together in a dialogue of life, give expression to the wideness of God's hospitality and grapple with the difficulties as well as the richness and promises of a shared life. In a world where religious and cultural differences often lead to conflict, it is increasingly important to search for missiological responses that assist in building inclusive communities and forging bonds of respect and understanding. Helen Richmond draws on the lived experience of Muslims and Christians in interfaith marriages in Indonesia and Australia, whose lives embody a living dialogue between two religious traditions, to offer a fresh approach to our understanding of Christian mission and Muslim da'wah. The narratives and testimonies of the couples in this study invite the question of whether Muslims and Christians who have viewed each other as intimidating opponents might instead regard each other as fellow pilgrims and partners in God's work in the world.